Comparative Analysis on Stress State of Submerged Floating Tunnels in Different Anchor Cable Arrangement Modes. (2016) - Lin, Fang; Mengjun, Wu; Guangdi, Wang; Peng, Cao
Abstract: Compared with submerged floating tunnels with other supporting systems, anchor cable type submerged floating tunnel is characterized by flexible structure arrangement, wide applicability and economical advantage. However, the mechanical features are obviously different under different anchor cable arrangement modes. By numerical calculation, structural displacement, bending moment and strength and distribution characteristics of axial force of anchor cable under the action of static load, wave load and water flow load are comparatively analyzed and applicable scopes of different anchor cable arrangement modes are given.